Epileptic seizure: always trouble or sometimes deliverance? - V. A. Karlov (Эпилепсия и пароксизмальные состояния)
The article presents three case reports confirming the phenomenon of “forced EEG normalization” described by Hans Landolt and the results of observation of four patients with mesotemporal epilepsy.